Effect of Syzigium cumini (pulp) extract on malondyaldehyde and blood pressure in chronic restraint stress rat - Mega Febia Suryajayanti; Anggi Laksmita Dewi; Bira Arumndari Nurrahma; Ayu Dwi Silvia Putri; Zunamilla Khairia; Arta Farmawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
ABSTRACTIntroduction. Chronic stress disturbs the equilibrium of oxidant-antioxidant redox in the human body which accelerates cellular aging. This condition promotes earlier onset of age-related diseases. Human body needs exogenous antioxidant to fight stress. Syzigium cumini has high antioxidant activity because it’s rich in anthocyanin. It has potential to become natural antioxidant source thus it needs to be developed.Aim. This study aims to investigate the effect of Syzigium cumini (Pulp) extract on the stress biomarkers which are Malondialdehyde and blood pressure in rat induced by restraint stress.Method. Chronic stress phase is conducted with male Wistar rats (n=20) which were divided into 4 groups (normal control, negative control, and two treatment groups with the ethanol extract of Syzygium cumini (Pulp) at 20 mg/200 gram and 40 mg/200 gram body weight). Restraint stress was carried out by placing the animal in narrow tube for 30 minutes daily (7 days). Blood pressure was evaluated before and after the treatment while Malondialdehyde was evaluated after the treatment. The One-way ANOVA was used to analyze the parameters.Results. Based on chronic stress phase, treatment groups show significant result in preventing the increase in blood pressure (P < 0,001). The increased levels of Malondialdehyde were prevented significantly in all treatment groups (P < 0,001)Conclusion. In chronic stress phase, Syzygium cumini (Pulp) extract can become an antihypertensive agent. Syzygium cumini (Pulp) extract shows an effect in decreasing lipid peroxidation products. This result shows that the Syzygium cumini (Pulp) extract has potent antioxidant function.Keywords. Syzigium cumini, restraint stress, malondialdehyde, MDA, blood pressure